PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN JAMAAH UMRAH PADA PT. PANDI KENCANA MURNI PEKANBARU - ', Restika; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research aims to examine the effect of service quality on Umrah pilgrims' satisfaction. The population of this research is alumni of the PT. Pandi Kencana Murni Pekanbaru congregation in 2023. This sampling technique uses the Probability Sampling method with a Porposive Sampling approach. The number of samples in this study was 80 congregations. The data analysis technique used in this research is Deskriptif statistics. Hypothesis testing in this research was carried out using the t statistical test. The data analysis technique used in this research is simple linear regression analysis and multiple linear regression using the Statistical Product and Service Solution (SPSS) version 19.0 for Windows data processing software program. The results of this research show that service quality has a significant effect on the satisfaction of Umrah pilgrims as evidenced by the results of the F-test seen in table 5.8. It can be explained that the F value = 53,850 with a significance of 0.000 at alpha 0.05 of the X variable (service quality) together. -sama has a significant influence on variable Y (congregation satisfaction). Keywords: Service Quality, Congregation Satisfaction